El principio de concentración en el derecho sustantivo y procesal (Research, Society and Development, 2022)
This study aims to evaluate the application of the principle of concentration in registration and the protection of the parties in property acquisition in Brazil, compare it to different legal systems, notably Portuguese and German, in order no analyze its efficiency and the possibility of future changes. The Brazilian registration system is very similar to the Portuguese one, both with juris tantum presumption and different from the German system that has juris et de jure presumption. The principle of concentration is applied in Brazilian real state law, which aims to guarantee the integrity of property acquisition, protecting the third party in good faith. With the emergence of the legal act 13.097/2015 and the Code of Civil Procedure/2015, new norms about transmission and protection of the acquirer in good faith were instituted. Furthermore, with the sole paragraph of the article 1,247 of the Civil Code there was a relativization of the protection given to the proprietor, that guarantees the transmission a non domino. Thereby, the survival of the article 1,247, sole paragraph, of the Civil Code in view of the wording of art. 54, sole paragraph of the legal act 13.097 / 2015 is at risk. It is up to the jurisprudence of STJ to interpret the law and limit the tension between the owner and the third party in good faith. For the development of the work, it was carried out an extensive doctrinal and jurisprudential research. In conclusion, legislative changes were suggested inspired by the German system with application of the principle of abstraction.